Current pediatric stroke treatment. - Grunwald, I; Kühn, A (2011)
BACKGROUND: The treatment of stroke in children and infants is essential, but unfortunately is not supported by factual and substantiated data. METHODS: This is a comprehensive review of the currently published data on acute ischemic stroke treatment in children and highlights recent advances and possibilities with mechanical devices in the treatment of stroke in this vulnerable age population. RESULTS: The current treatment for most children with acute ischemic stroke is limited to the management of the symptoms. Mechanical recanalization may improve recanalization rates and clinical outcomes. CONCLUSIONS: Although clinical trials will be difficult to establish in children, continued research and additional experience are imperative to treat this often devastating condition.